2018
DOI: 10.1080/24750573.2018.1480855
|View full text |Cite
|
Sign up to set email alerts
|

Is there any association between antidepressants and restless legs syndrome in a large Turkish population receiving mono or combined treatment? A cross-sectional comparative study

Abstract: OBJECTIVE: Here, we aimed at investigating whether the treatment with antidepressants is associated with restless legs syndrome (RLS) and at determining the effects of mono or combined antidepressant therapy on the patients with RLS. METHODS: Five hundred and fifty-five patients with RLS receiving mono or combined antidepressant therapy were included in the study group, and 555 individuals with no history of the use of antidepressants constituted the control group. The diagnosis of restless leg syndrome was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…In contrast to our results, Odabaş and Uca (2018) clarified that the use of antidepressant drugs had limited association with RLS. -5 of 8…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our results, Odabaş and Uca (2018) clarified that the use of antidepressant drugs had limited association with RLS. -5 of 8…”
Section: Discussioncontrasting
confidence: 99%
“…On the contrary, there was improvement in the prevalent symptoms of RLS with the use of SSRIs [16]. In a study conducted in our country the prevalence of RLS was found as 5.9% among the controls, and 9.2% among the patients being treated with antidepressants and the difference between both groups was statistically significant at borderline [15] (p = 0.053).…”
Section: Discussionmentioning
confidence: 75%
“…In addition, Baughman and colleagues found no significant risk of RLS development in patients using combined antidepressants [39]. In another study conducted by Odabas and Uca no statistically significant difference was determined between the groups receiving mono or combined treatment [15].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For 1990 and 2019, a total of 52 reports containing 179 individuals that developed a MD associated with MTZ were identified from 20 different countries [ Table 1 ] [ 10 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 ]. 103 individuals were from European countries, 49 Asian, 17 Australian, 8 North American, and 2 South American.…”
Section: R Esultsmentioning
confidence: 99%